Between Islamic and Western Education: The Educational Dichotomy in ‘Abd al-Raḥmān al-Naḥlāwī’s Thought - Ahmad Natsir; Didin Wahyudin; Hafidh Aziz; Hasbulloh Nadaraning (MUSLIM HERITAGE, 2025)
This research aims to invigorate the discourse on the educational thought of Al-Nahlawi, a figure frequently referenced yet seldom critically examined in Indonesia. Specifically, this study aims to: (1) Analyze the major ideas and ideological underpinnings of Al-Nahlawi's thoughts; (2) Trace the influence of the socio-political context of Syria on his work; and (3) Reveal the dichotomization of Western vs. Islamic education in his discourse. To achieve these objectives, this study employs the method of hermeneutic analysis to examine his major ideas and critical discourse analysis based on Fowler's model to investigate the diction and underlying ideology of his language. The research concludes that: Al-Naḥlāwī's thinking was significantly influenced by Syria's political dynamics and his concerns about the Islamic revival, which led him to adopt a stance of resistance against the West. His central idea focuses on returning humanity to its innate nature (fitrah) through the application of ideal Islamic educational principles, covering objectives, subject matter, curriculum, and methods. The primary conclusion of this study is that Al-Naḥlāwī's critique of Western education—which he describes with vocabulary such as "calamity," "disbelief" (kufr), and "non-integral"—not only constructs a sharp dichotomy but also affirms that his work is a form of ideological resistance, clearly represented in all its elements. Abstrak Penelitian ini bertujuan untuk meramaikan diskursus tentang pemikiran pendidikan Al-Nahlawi, seorang tokoh Pendidikan Islam yang sering dirujuk namun jarang dikritisi secara mendalam di Indonesia. Secara spesifik, tujuan penelitian ini adalah untuk: (1) Menganalisis gagasan besar dan relasi ideologi dalam pemikiran Al-Nahlawi; (2) Menelusuri pengaruh konteks sosio-politik Suriah terhadap karyanya; dan (3) Mengungkap dikotomi pendidikan Barat vs. Islam dalamwacananya. Untuk mencapai tujuan tersebut, penelitian ini menggunakan metode analisis hermeneutika untuk mengulas gagasan besarnya dan analisiswacanakritis model Fowler menginvestigasi diksi serta ideologi yang mendasari bahasanya. Hasil penelitian menyimpulkan bahwa pemikiran Al-Naḥlāwī sangat dipengaruhi oleh dinamika politik Suriah dan kegundahannyaakankebangkitan Islam, yang mendorongnya pada posisi perlawanan terhadap Barat. Gagasan inti ini berfokus pada pengembalian umat manusia kepada fitrah penerapan prinsip-prinsip pendidikan Islam yang ideal, mencakuptujuan, materi, kurikulum, hingga metode. Simpulan utama penelitian ini adalah bahwa kritik Al-Naḥlāwī terhadap pendidikan Barat—yang digambarkannyadengankosa kata seperti "musibah", "kufur", dan "tidak integral"—tidak hanya membangun dikotomi yang tajam, tetapi juga perlawanan ideologis yang terepresentasi secara jelas dalam seluruh unsurnya.